Effect of Yttrium Contents on the Microstructure of a Hot-Rolled Tantalum-Containing 12Cr-ODS Steel - Wang, Changhao; Luo, Jinru; Guo, Ning; Tu, Jian; Ye, Hong; Zhang, Pengcheng; Yan, Qingzhi (Frontiers in Materials, 2019)
Dual-phase oxide dispersion strengthened (ODS) steels of Fe–12Cr–xY (x=0.1, 0.2 and 0.3 wt%) have been fabricated by casting, hot-forging and subsequent hot-rolling. Microstructure of the hot-rolled samples was carefully characterized by use of electron probe microanalysis (EPMA), electron backscatter diffraction (EBSD) and transmission electron microscope (TEM). The results show that all the samples consist of ferrite phase with coarse fiber grains (elongated along the rolling direction) and martensite phase in the form of fine block grains. As the Y addition increases, the ratio of ferrite to martensite and density of low-angle boundaries (LABs) within the martensite and ferrite grains do not change significantly. The Y2O3 particles introduced by self-oxidation during casting are survived without being dissolved or refined after hot-forging and hot-rolling. However, as the Y addition increases, the Y2O3 particles tend to aggregate with fine M23C6 and TaC carbides. The hardness of the sample with high Y additions is lower than that of the samples with none or low Y additions, which could be attributed to the aggregation coarsening of the yttria and TaC particles, resulting in a decrease in dispersion strengthening effect. The effect of Y additions on microtexture was also discussed.